Collaborations for student success how librarians and student affairs work together to enrich learning - Long, Dallas (Beta Phi Mu scholars., 2019)
By using multiple focus groups, Long describes the experiences and perceptions of librarians and student affairs professionals at several four-year, residential colleges and universities. This book is the perfect road map for librarians and student affairs professionals alike who are seeking partners for campus collaborations.